Strategi Pengelolaan Sampah Rumah Tangga Berbasis Komunitas di Desa Sambirejo, Kabupaten Pasuruan - Meirezaldi, Onni; Worokinasih, Saparila; Fahrudi, Agung N.L.I; Prafitri, Rizki; Hapsari, Addelia P.; Anam, Afrizal K.; Karimah, Awalinda; Margaretha, Eirine D. A.; Putri, Hajeng P. A.; Sazkiya, Lubna D.; Panjaitan, Natanael; Muhana, Naufal A.; Fadhila, Nia A.; Achmadinata, Raihan R. D.; Ali, Shofan H.; Wahyuni, Tri; Awilia, Zefanya (Abdimas Indonesian Journal, 2025)
Sambirejo Village in Rejoso District, Pasuruan Regency, experiences major challenges in household waste management due to population growth and increased economic activities. This program addressed these challenges by improving environmental quality and community welfare. The main objective was to empower residents through capacity-building sessions on waste sorting, composting, and using Lumbricus Rubellus worms and Black Soldier Fly (BSF) maggots for organic waste reduction. Program implementation began with a survey identifying community needs, followed by workshops and hands-on training emphasising participatory methods. These sessions introduced the principles of 3R (Reduce, Reuse, Recycle), home-scale composting, and the formation of community-based waste management groups. Results indicated a notable increase in public awareness regarding proper waste disposal, a decline in illegal dumping sites, and broader adoption of organic waste processing technologies. Although the community’s improved understanding of waste segregation and composting reflected a positive shift in behaviour, limited facilities and varying levels of commitment continued to pose challenges. Overall, this initiative highlights the effectiveness of a collaborative and community-driven approach in addressing waste management issues. Sustained government support, academic engagement, and strong community participation are vital to ensure the long-term impact of these efforts and provide a practical model for other villages facing similar environmental problems.